Criminological characteristics of criminal activity fictitious companies in Ukraine, as the basis for the activities of conversion centers - Воробей, Олена Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article the criminalistic characteristics of criminal activities of fictitious companies in Ukraine, as the basis for the activities of conversion centers. The author summarizes the statistical indicators of fictitious business in Ukraine, especially the establishment of such companies and their functioning. Researched and their classification by purpose of use and the subjects of registration and also found features of investigation of criminal offences related to the activities of fictitious companies. Today, despite political change, the fight against corruption and the desire of the authorities to stabilize the economy, Ukraine continues to apply the criminal scheme to launder funds through the use of so-called "conversion centers", or as they are called in the people, "firms-butterflies", whose activities cause the state billions of dollars in economic losses The detection and investigation of economic crimes is often stated that a binding element of their mechanism acts fictitious business (article 205 of the criminal code of Ukraine). This crime is inherently subordinate to and can be associated with the Commission and concealment of many economic crimes, aimed at obtaining material benefits. Law enforcement practice shows that at the stage of preparation of the financial fraud criminals carried out the state registration of fictitious companies or acquiring existing firms. Based on the author’s research, illegal financial transactions that use fictitious companies, divided into two groups depending on the purpose of such use: 1) withdrawal of funds in the "shadow" sector of the economy through the legalization of an existing business entity of inventory actually purchased for cash; the price adjustment of inventory actually purchased for cash and on credit (informally) and for clearing (officially), with the aim of increasing total gross expenditures real entity with a corresponding reduction of the object of taxation; direct adjustments total gross expense of the real entity with the aim of reducing the object of taxation without actual receipt of goods (works, services); conversion of funds for their further use in various areas, including for purchasing goods and services for cash; 2) money laundering, proceeds of crime, through the use of circuits (circuits) movement of goods, in which between real entities is fictitious firm, through which is directed the movement of goods, for the purpose of adjustment of their ultimate cost; documentation of the flow of goods which has actually been exercised for cash; adjust prices real existing entities in cases where the goods they are implemented informally at a higher price, at the same time making expenses was made by a fictitious firm at a lower price to reduce officially received aggregate gross income and reduce tax liabilities money laundering, which is in shadow turnover, with the purpose of investment, capital investment, acquisition of real estate, securities and the like. Thus, crimes committed through the use of fictitious companies, has acquired a dimension that increasingly threaten the economic security of Ukraine because largely thanks to this technology, a portion of the capital of the country is in shadow turnover. Fictitious business acquired spread not only in the financial sector, but also in other key sectors of the economy – fuel and energy complex, coal and metallurgical industries, agro-industrial complex. According to local experts-economists, more than 25 % of firms that are created in Ukraine, intended for use in an uncontrolled economy.